Pedagogical Leadership of the Principal at SMP Negeri 1 Banggai and SMP Negeri Satap Tolokibit - Marto Potimbang; Arifin Suking; Zulystiawati Zulystiawati (International Journal of Education, Culture, and Society, 2026)
Schools with complete facilities and those with limited resources face distinct challenges in implementing pedagogical leadership, thereby requiring adaptive and context-sensitive strategies. This study aims to analyze the principal’s pedagogical leadership in: (1) developing teachers’ pedagogical competence, (2) improving teachers’ professional competence, and (3) building a culture of teacher learning. The research was conducted at SMP Negeri 1 Banggai and SMP Negeri Satap Tolokibit using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation and analyzed using a comparative analysis model. The findings reveal that pedagogical leadership in both schools contributes to strengthening teachers’ confidence in managing learning, encouraging greater reflectiveness, and fostering openness to instructional improvement. Although the principals in both schools share similar orientations and goals, their leadership is enacted through different strategies shaped by each school’s context. In addition, principal leadership plays a strategic role in enhancing teachers’ professional competence by reinforcing motivation, supporting contextual continuing professional development, and promoting collective learning. The study further shows that the principals’ pedagogical leadership successfully cultivates a culture of teacher learning through different yet complementary strategies aligned with the characteristics and conditions of each school. These findings underscore that effective pedagogical leadership is not uniform in practice but must be contextually adapted to strengthen teacher competence and sustain a culture of professional learning across diverse school settings.